Seeing is Believing? Evidence from a Demonstration Plot Experiment in Mozambique - Kondylis, Florence; Mueller, Valerie (International Food Policy Research Institute, 2012)
We preliminarily find that providing sustainable land management (SLM) training to standard contact farmers and having them maintain demonstration plots within the community on a whole had low impact on the knowledge and adoption of SLM practices. However, the aspect of our intervention that targeted a traditionally disadvantaged group as far as their access to extension services, women, was somewhat successful in terms of improving their SLM knowledge and adoption rates. Having a female contact farmer increased the number of SLM techniques adopted by women by 10 percent. Both male and female farmers in this treatment group identified female (not male) contact farmers as a source of learning for both SLM practices and non SLM-practices suggesting knowledge spillovers. Furthermore, farmers were additionally inclined to teach others what they have learned in the communities with female contact farmers. While we are currently analyzing additional factors that may affect the ability of the intervention to influence behavior, our results have broader implications for improving extension services overall.